Tinajuan Maslahah Terhadap Mandatory Sertifikasi Halal Dalam Undang-Undang No. 33 Tahun 2014 Tentang Jaminan Produk Halal Di Indonesia - Muhammad Farich Maulana; Shofiyun Nahidloh (Journal of Creative Student Research, 2023)
In Islam, the halalness of the food consumed is a very basic principle, therefore the state is obliged to provide protection and guarantees regarding the halalness of the products consumed and used by the community. The government seeks to stabilize and regulate the flow of products circulating in Indonesia so that Law Number 33 of 2014 concerning Halal Product Guarantee is established. Before PP 31 of 2019 was issued, the halal certification process was still carried out by MUI. However, after PP 31 of 2019 was issued, the authority to issue halal certification rests entirely with BPJPH as the leading Halal Product Assurance sector. The move has drawn a lot of criticism because BPJPH is considered to be still not ready to implement the program, as is the case with infrastructure and information systems. The transfer of authority should have been as mandated by the Law on Halal Product Guarantee, but until the time specified BPJPH is not yet fully ready to become a regulator of halal product assurance in Indonesia. The results of this study can be concluded that BPJPH is ready to be a pioneer in determining halal product guarantees which were previously the authority of MUI. Mandatory halal certification is categorized as maslahah because it relates to the basic needs of mankind in the world and the hereafter and does not contain any harm.